Composer classification of Filipino song lyrics using machine learning - Chan, Oliver Isaac; Sadornas, Patrick Joseph; Cabredo, Rafael; Cheng, Charibeth (Philippine computing journal)
We implemented a machine learning technique using artificial neural network to perform composer classification (authorship attribution) of songs with lyrics primarily written in Filipino...